Clinical Features and Outcomes of Adrenal Cavernous Hemangioma: A Study of 8 Cases from a Single Center. (28th April 2021) - Huang, Henghai; Wu, Xiaoyun; Lin, Xiaocao; Li, Delin; Zeng, Jingjing
Abstract : Background . Cavernous hemangioma is a rare benign tumor that develops from the adrenal glands. In this study, we present our experience with patients with adrenal cavernous hemangiomas (ACH) in a Chinese population. Methods . Demographic, diagnostic, surgical, and pathological findings in patients at a single institution who were adrenalectomized as a result of ACH were retrospectively reviewed. Results . Among 601 patients who underwent adrenalectomy, 8 (1.33%; 5 men, 3 women) cases were diagnosed with ACH between January 1, 1998, and December 31, 2018, in a single institution. The mean age was 53.25 ± 11.9 years (range, 35–67 years). Four (50%) were asymptomatic, and three (37.5%) complained of abdominal or flank discomfort. Preoperative computed tomography (CT) revealed ACH in 3 (37.5%) cases. Well-defined borders and heterogeneous enhancement with characteristic progressive partial filling-in were characteristic CT features of ACH (tumor size>3 cm). The mean tumor size was 5.16 ± 3.4 cm (range, 1.5–11 cm). No recurrence occurred during a median follow-up period of 38.37 months (range, 8–60 months). Conclusions . ACH was asymptomatic in most cases, and diagnosis could be challenging. Adrenalectomy is a safe treatment modality for ACH, and it ensures favorable outcomes.